Using Social Media to Communicate Sustainable Preventive Measures and Curtail Misinformation - Hauer, Michael K.; Sood, Suruchi (Frontiers in Psychology, 2020)
Effective crisis and risk communication strategies are crucial to promote preventive measures, particularly during times of emergency such as the global COVID-19 pandemic. With its global reach, social media is a key source of news and information about COVID-19. However, the abundance of misinformation about personal protective measures that people post on social media, makes it imperative to develop a deeper understanding of effective messaging strategies. Improving the quality of information and strategy with which it is disseminated through social media is crucial to minimizing anxiety, panic and improving the adoption of sustainable preventive measures in addition to curtailing misinformation. Understanding the components of effective health communication strategies allows us to glean common methods to address misinformation which in turn lead to people adopting the appropriate preventive measures. The purpose of this article is to understand how effective social media communication strategies can be crafted to promote sustainable preventive measures and curtail wide-spread misinformation. Health organizations as well as communications organizations have made available information for effective social media messaging and more importantly serve as a gateway to other resources. We review their recommendations to identify common social media communication elements on the adoption of sustainable preventive measures and effective strategies for curtailing misinformation. We further review social media messaging during the Ebola and Zika outbreaks to evaluate the success of social media strategies and draw from lessons learned. We then create a set of best practices for developing and disseminating social media messaging regarding COVID-19.